Report - Weymouth & District General Strike Committee, received 7 May 1926 (page 2)
1926-05-07 "Report - Weymouth & District General Strike Committee, received 7 May 1926 (page 2)" [g0347002.jpg], 7 May 1926, Weymouth & District General Strike Committee